1990
DOI: 10.1021/jm00170a009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a new class of 2,3-dihydro-2-oxo-1H-benzimidazole-1-carboxylic acid derivatives as highly potent 5-HT3 receptor antagonists

Abstract: A series of 2,3-dihydro-2-oxo-1H-benzimidazole-1-carboxylic acid esters and amides containing a basic azacyclo- or azabicycloalkyl moiety has been synthesized and evaluated for 5-HT3 antagonistic activity in a radioligand binding assay ([3H]ICS 205930) and in the 5-HT-induced von Bezold-Jarisch reflex in the rat. It was found that endo-substituted azabicycloalkyl derivatives (e.g. 7a, 12a, 12b) were much more active than the corresponding exo analogues (e.g. 7b, 12h, 12i) or azacycloalkyl compounds. Amidic der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 3 publications
4
36
0
Order By: Relevance
“…An alternative was to use the azabicycloalkyl benzimidazolone derivative, DAU 6285 (Turconi et al, 1990), a drug that we found to inhibit cyclic AMP production induced by specific 5-HT4 receptor agonists in cultured colliculi neurones (Dumuis et al, 1992). At a concentration of 10 gM, DAU 6285 had no effect by its own on K+ currents of colliculi …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative was to use the azabicycloalkyl benzimidazolone derivative, DAU 6285 (Turconi et al, 1990), a drug that we found to inhibit cyclic AMP production induced by specific 5-HT4 receptor agonists in cultured colliculi neurones (Dumuis et al, 1992). At a concentration of 10 gM, DAU 6285 had no effect by its own on K+ currents of colliculi …”
Section: Methodsmentioning
confidence: 99%
“…BIMU 8 and more classically renzapride (Turconi et al, 1990) also display 5-HT3 antagonistic activity in receptor binding assays and physiological tests. However, it seems unlikely that this property of BIMU 8 and renzapride accounted for the drug effects observed here on the K+ current in colliculi neurones since another potent and specific 5-HT3 antagonist, ondansetron, did not alter the current.…”
Section: Pharmacology Of the S-ht-induced Inhibition Of The K+ Currentmentioning
confidence: 99%
“…In the last few years a novel class of 5-hydroxytryptamine3 (5-HT3) receptor antagonist has been synthesized (Turconi et al, 1990) and the potency and selectivity of these new molecules have been tested in isolated preparations and in vivo models. Among these compounds, DAU 6215 (endo-N- (8-methyl-8-azabicyclo-[3.2.…”
Section: Introductionmentioning
confidence: 99%
“…Among these compounds, DAU 6215 (endo-N- (8-methyl-8-azabicyclo-[3.2. 1]-octo-3-yl)-2,3-dihydro-2-oxo-lHbenzimidazole-l-carboxamide hydrochloride), a benzimidazolone derivative, exhibits a high affinity for the [3H]-ICS binding site in rat brain tissue, and it is equipotent with ICS 205-930 in inhibiting 5-HT-induced bradycardia in rats (Turconi et al, 1990;1991a). DAU 6215 was also found to be a weak, partial agonist at the 5-HT4 receptor, as demonstrated by the ability of this compound to stimulate adenosine 3':5'-cyclic monophosphate (cyclic AMP) production in colliculi neurones in cultures (Dumuis et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Examples were the best suitable diastereomer did not exceed the activity of the aminopiperidine derivative include analogues of the analgesic fentanyl 12 (decahydroquinoline type [108], isoquinuclidine type [101,109], tropane type [110], granatane type [111] and norcamphidine type [94]), of the neuroleptic Pipamperone 1 (azabicyclohexane type [64]) or of the analgesic piritramide 2 (azabicyclohexane type [72]). A clear improvement of activity, however, was performed with the substances 102 (analogue of bamipine 6 and 15 times more active [76,83]), 103 (analogue of Clebopride 9 and 30 times more active [26]) and 104a (300 times more active than the analogous aminopiperidine derivative [27]) (Fig. 14).…”
Section: Discussionmentioning
confidence: 99%